Dynamics of Excel, IBM PC edition - Yu, John W.; Demers, Catherine (Illinois : Dow Jones-Irwin, 1989)
The focus of this book is Excel for the IBM, a comprehensive spreadsheet program developed by Microsoft Corporation. version 2.0 was released for the IBM and compatibles in November 1987, and Version 2.1 ws released in October 1988. This book covers the feature of both versions of Excel.
Introduction -- 1. Installing excel and getting to know the program -- 2. Building a basic worksheet -- 3. Editing and formatting -- 4. Formulas and functions -- 5. Tapping the power of functions -- 6. Using advanced functions -- 7. Multiple windows -- 8. Using arrays and data tables -- 9. Array functions -- 10. Charting worksheets -- 11. Database management -- 12. Basic macros -- 13. Macro functions and macro programming -- 14. Creating your own functions -- 15. Importing and exporting worksheet data.
Includes index.
Keywords: COMPUTER PROGRAMMING